PERSEPSI GENERASI Z MAHASISWA VOKASI PENERBANGAN TERHADAP ETIKA DALAM KOMUNIKASI DIGITAL - Fatkhulloh, Amal; Kurniawanto, Hari; Arrafat, Bhima Shakti; Widyantoro, Arsanto Noorwahyu; Widagdo, Rinosa Ari (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the perceptions of Generation Z aviation vocational students regarding ethics in digital communication. This study uses a descriptive quantitative approach. The sample in this study was 100 active students from the Generation Z category selected through a purposive sampling technique. The data collection technique used a questionnaire distributed through Google Forms. The data analysis used in this study was descriptive statistics. The results of this study indicate that aviation vocational students from Generation Z show a relatively high level of ethical awareness in conducting digital communication, especially in terms of politeness, honesty, and a sense of responsibility for the content conveyed. However, aspects of appropriate language use and awareness of the importance of maintaining digital privacy still require more attention. Therefore, ongoing educational efforts and training are needed so that the values of professionalism and integrity can be further ingrained in students as future professionals in the aviation industry who uphold work ethics.